DIFFICULT CONCEPTS IN NIGERIAN SENIOR SECONDARY SCHOOL MATHEMATICS CURRICULUM AS PERCEIVED BY STUDENTS - ADENIYI, Comfort Olawumi; AKINOSO, Sabainah Oyebola (Ilorin Journal of Education, 2023)
This paper examined students' perceived difficult concepts in Nigerian Secondary School Curriculum in Nigeria. The population for the study was all Senior Secondary School Students in Education district VI of Lagos State. The sample consisted of 250 SSS3 students selected from science, art, and commercial classes using stratified random sampling techniques. The instrument for data collection was a researcher designed questionnaire titled Difficult Concept Identification Questionnaire in Mathematics (DCIQM) with a reliability value of 0.74. The instrument was based on the current national Mathematics curriculum for senior secondary school. Frequency counts and mean were used to analyzing the data collected. The study revealed that students have difficulties in handing some concepts in mathematics especially the application of different concepts in mathematics. Besides, the study also discovered that most teachers deliberately jump some recommended topics in the curriculum. The study recommended among other that teachers should ensure that all required topics in the syllabus are properly treated and learner-centered method should be employed in the teaching of mathematics to allow active students participation and easy assimilation of mathematical concepts.